2019
DOI: 10.1088/1757-899x/523/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of warm springs in the Ie Brôuk hydrothermal areas at Aceh Besar district

Abstract: Indonesia is a country with the largest geothermal potential resource in the world, estimated of 28,617 MW or equivalent to 40% of the world’s geothermal potential. Geothermal energy is environmentally friendly and quite economical compared to fossil energy. Seulawah Agam is one of Indonesia’s geothermal fields that has several manifestation zones, including Ie Brôuk (BH1 and BH2) manifestations. The analysis for this study was conducted by acid-base titration, UV-Vis Spectrophotometry and Atomic Absorption Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, the energy storage capacity of batteries is very limited, and for this reason some scientists are attempting to discover another type of energy storage materials that can store significant amount of energy [11][12][13].Calcium is one of the most abundant metals on earth. It can be mostly found as an ion in seawater [14], as well as geothermal hot springs [15][16][17][18]. It can be also found as an oxide in limestone and fossilized remnant sites [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the energy storage capacity of batteries is very limited, and for this reason some scientists are attempting to discover another type of energy storage materials that can store significant amount of energy [11][12][13].Calcium is one of the most abundant metals on earth. It can be mostly found as an ion in seawater [14], as well as geothermal hot springs [15][16][17][18]. It can be also found as an oxide in limestone and fossilized remnant sites [14].…”
mentioning
confidence: 99%
“…Calcium is one of the most abundant metals on earth. It can be mostly found as an ion in seawater [14], as well as geothermal hot springs [15][16][17][18]. It can be also found as an oxide in limestone and fossilized remnant sites [14].…”
mentioning
confidence: 99%
“…The variation is caused not only by the type of plant but also by the geological and geographical origins of the plant. The plant that grows in high salinity areas like geothermal [22][23][24] or limestone contains more various and higher metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Some research showed that the secondary metabolite content of plants taken from geothermal areas is higher in species diversity and yields than plants from ordinary areas [23][24][25][26] In Aceh Province, there are several areas that have geothermal potential due to volcanic activity [27][28][29], one of which is Seulawah Agam Mountain in Aceh Besar District [30][31][32]. This mountain has several manifestations in several separate locations, namely the manifestation of Ie Brouk [33,34], Ie Seu-Um [35,36], and Ie Jue [37,38]. Lots of mineral-rich water in each of these manifestations spread to the surrounding environment so that it affects the mineral composition of the soil to the biosynthesis of plants that grow in that area [33].…”
Section: Introductionmentioning
confidence: 99%